Response of Acropora digitifera to ocean acidification: constraints from d11B, Sr, Mg, and Ba compositions of aragonitic skeletons cultured under variable seawater pH - Tanaka, K.; Holcomb, M.; Takahashi, A.; Kurihara, H.; Asami, R.; Shinjo, R.; Sowa, K.; Rankenburg, Kai; Watanabe, T.; McCulloch, M. (Springer Verlag, 2015)
© 2015, Springer-Verlag Berlin Heidelberg. The response of Acropora digitifera to ocean acidification is determined using geochemical proxy measurements of the skeletal composition of A. digitifera cultured under a range of pH levels. We show that the chemical composition (d11B, Sr/Ca, Mg/Ca, and Ba/Ca) of the coral skeletons can provide quantitative constraints on the effects of seawater pH on the pH in the calcification fluid (pHCF) and the mechanisms controlling the incorporation of trace elements into coral aragonite. With the decline of seawater pH, the skeletal d11B value decreased, while the Sr/Ca ratio showed an increasing trend. The relationship between Mg/Ca and Ba/Ca versus seawater pH was not significant. Inter-colony variation of d11B was insignificant, although inter-colony variation was observed for Ba/Ca. The decreasing trend of pHCFcalculated from d11B was from ~8.5, 8.4, and 8.3 for seawater pH of ~8.1, 7.8, and 7.4, respectively. Model calculations based on Sr/Ca and pHCFsuggest that upregulation of pHCFoccurs via exchange of H+with Ca2+with kinetic effects (Rayleigh fractionation), reducing Sr/Ca relative to inorganic deposition of aragonite from seawater. We show that it is possible to constrain the overall carbonate chemistry of the calcifying fluid with estimates of the carbonate saturation of the calcifying fluid (OCF) being derived from skeletal Sr/Ca and pHCF(from d11B). These estimates suggest that the aragonite saturation state of the calcifying fluid OCFis elevated by a factor of 5–10 relative to ambient seawater under all treatment conditions.